Management of seasonal dermatitis in horses by using leaf extract of Aerva javanica (Indian Journal of Traditional Knowledge (IJTK), 2024)
Occurrence of seasonal allergic dermatitis, especially insect bite hypersensitivity and atopic dermatitis are very common in horses. At present there is no satisfactory treatment is available for management of these skin allergies. Plant flavonoids such as quercetin, kaempferol and their glycoside derivatives have been reported for their anti allergic and anti-inflammatory properties. In present study we have prepared an extract from the leaves of Aerva javanica, which was found effective to manage clinical cases of seasonal allergic dermatitis in horses. Clinical signs of the allergic dermatitis in horses were alopecia, thickening of skin and itching. On histopathological examination of skin biopsy samples taken from the clinical cases epidermal hyperplasia, orthokeratotic and parakeratotic hyperkeratosis, spongiosis, occasional trichomalacia, multifocal areas of aggregation of lymphocytes with or without infiltration of eosinophils were observed. Mass spectrometer analysis of more purified extract suggested a glycoside of kaempferol may be an active ingredient of the extract.